A161 MACROSCOPIC AND HISTOLOGY FINDINGS DURING UPPER DIGESTIVE ENDOSCOPY IN CHILDREN WITH SUSPICION OF CELIAC DISEASE AND HIGH LEVELS OF TRANSGLUTAMINASE IGA-ANTIBODY. (26th February 2020) - Jantchou, P; Dirks, M; Grzywacz, K; Marchand, V; Halac, U; Groleau, V; Patey, N; Dal Soglio, D; Oligny, L; Drouin, E; Deslandres, C
Abstract: Background: The European Society of Pediatric Gastroenterology Hepatology and Nutrition suggests that the diagnosis of Celiac disease (CD) can be confirmed solely on the basis of clinical symptoms and bloodwork including a level of transglutaminase IgA-antibodies (TGA) ≥ 10 times the upper limit of normal (10XN). In Canada and the United States, this recommendation has not been endorsed. We recently demonstrated that TGA ≥ 10XN performed at our institution ( INOVA Diagnostics' Quanta Lite ) was a reliable predictive test of villous atrophy in patients with suspicion of CD. Aims: The aim of the present study was to investigate the rate of supplemental endoscopic or histological findings in a cohort of children with TGA ≥ 10XN and the association of these findings with clinical symptoms. Methods: Consecutive children with suspected CD who had an endoscopy between 2011 and 2018 were included in this analysis. Data was extracted from our CD database. The macroscopic and histological findings were reported. We compared these diagnoses to the clinical symptoms. Results: From 2011 to 2018, 405 new cases of CD were identified in our pediatric center. In total, 238 (58.7%) patients had baseline TGA levels ≥ 10XN (67.2% females, median (IQR) age 8.4 (4.8–12.2)). The median interval between the first visit to the gastroenterology unit and the endoscopy was 43.0 (21.0–78.0) days. In total, 58% of the endoscopies had macroscopic findings in the bulb (37.8 %) or the duodenum (41.5%) including a mosaic pattern, mucosal fissuring, or erythema. Seven cases (2.8%) of esophagitis were identified during endoscopy; histological analysis confirmed eosinophilic esophagitis in 3 cases (1.2%) and peptic esophagitis in 4 cases. Non-specific gastritis was present in 58 patients (24.4%) and 2 cases of Helicobacter pylori infection were identified. The biopsies showed subtotal/total villous atrophy of duodenum in 171 (71.8%) or partial villous atrophy in 51 patients (29.8 %). Ten patients (4, 3%) had villous atrophy in the duodenal bulb alone, with normal biopsies of the second part of the duodenum. Abdominal pain did not correlate with gastritis or duodenitis. However, children with diarrhea had a greater prevalence of visible endoscopic inflammation in the duodenum than those without diarrhea: 53.5% vs 38.9% respectively; P= 0, 037. Conclusions: Apart from the classical features associated with CD, the supplementary diagnostic yield of endoscopy was low. There were only a few cases of additional diseases identified by the endoscopic procedure in a large cohort of children and adolescents with suspicion of CD. Therefore, these results support the no-biopsy approach in the settings of TGA ≥ 10XN using a reliable diagnostic kit. Funding Agencies: None